2021
DOI: 10.3390/pr9050793
|View full text |Cite
|
Sign up to set email alerts
|

Bead Geometry Prediction Model for 9% Nickel Laser Weldment, Part 1: Global Regression Model vs. Modified Regression Model

Abstract: Due to its excellent toughness and stiffness in cryogenic conditions, 9% nickel steel is applied to LNG storage facilities, and its usage is increasing as a result of changes in environmental regulations. A study was conducted on the development of a predictive model to optimize the laser welding process of 9% nickel steel, and two prediction models were developed using one hundred data points obtained through experiments. A global regression model used as a general prediction model and a modified regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Linear regression models were postulated for all of these characteristics by taking into account all major and multiple interrelationships. For predicting and evaluating input variables, several scholars have been using multiple regression [41][42][43]. The data from the design of experiment in Table 1 and the responses in Table 3 were utilized to generate the formulas.…”
Section: Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Linear regression models were postulated for all of these characteristics by taking into account all major and multiple interrelationships. For predicting and evaluating input variables, several scholars have been using multiple regression [41][42][43]. The data from the design of experiment in Table 1 and the responses in Table 3 were utilized to generate the formulas.…”
Section: Regression Analysismentioning
confidence: 99%
“…Such regression models were then used to estimate weld bead shape characteristics and dilution percentage. The postulated equations for the bead geometry are: Many researchers have used regression models for modeling and analyzing welding parameters [41][42][43][44]. It has been suggested that relative error should be less than 20% for statistical analysis to consider it to be reliable.…”
Section: Regression Analysismentioning
confidence: 99%